1996
DOI: 10.2165/00002512-199608020-00001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Amyloid Drugs

Abstract: The requirements for amyloidogenesis, as it is currently understood, include an adequate amyloid precursor pool, a nidus for fibrillogenesis, interactions with a set of common components (most of which are involved in basement membrane structure) and amyloid turnover. These factors serve as the basis for therapeutic attack. General strategies focusing on each of these factors are presented with examples from the experimental and clinical literature. These include reducing the amyloid precursor protein pool in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Thus, there have been considerable efforts to understand the mechanism leading to A␤ deposition (1,18). The primary motivation of these efforts is the expectation that they may aid in the development of a treatment of Alzheimer's disease based on inhibition of amyloid formation (19)(20)(21). Extensive x-ray diffraction and electron microscopy studies revealed that A␤ forms characteristic, ␤-sheet-rich fibrils, 6-8 nm in diameter, in which the direction of peptide chains is perpendicular to the axis of a fibril (22)(23)(24).…”
mentioning
confidence: 99%
“…Thus, there have been considerable efforts to understand the mechanism leading to A␤ deposition (1,18). The primary motivation of these efforts is the expectation that they may aid in the development of a treatment of Alzheimer's disease based on inhibition of amyloid formation (19)(20)(21). Extensive x-ray diffraction and electron microscopy studies revealed that A␤ forms characteristic, ␤-sheet-rich fibrils, 6-8 nm in diameter, in which the direction of peptide chains is perpendicular to the axis of a fibril (22)(23)(24).…”
mentioning
confidence: 99%
“…The amyloid fibrils are considered to be produced by the conformational changes from the α-helix to β-sheet rich structures . Thus, although there may be various therapautic strategies, stabilizing the α-helical conformation of the specific protein that inhibits its conversion into β-sheets appears to be the most fundamental therapeutic strategy. , Stabilizing the native fold of an amyloidogenic protein by a small molecule is also useful for preventing the conformational changes 1 The amino acid sequence of the Syrian hamster prion protein …”
mentioning
confidence: 99%